PROSEDUR PENGGAJIAN PADA BADAN PENDIDIKAN DAN PELATIHAN PEMERIKSAAN KEUANGAN NEGARA BPK RI - Meta Emelia Perangin Angin, (2021)
Procedure is a series of steps that are interrelated in order to complete a job in order to control the efficiency and effectiveness of the company. Payroll procedures can help the main activities in the company, to produce good procedures. Salary is payment for services performed by employees who work for one month. Salary plays a significant role in a company because salary is one of the driving factors in employee performance in providing good service, in order to ensure the welfare of employees who work in the company. The goal to be achieved is to find out the payroll procedure, the documents used in the payroll procedure, and the salary components used in the Education and Training Agency for the State Audit Board of the Republic of Indonesia.